Sarasehan Peningkatan Kapasitas dan Penanaman Pohon Produktif di Pondok Pesantren Nurul Iman Nw Bentek Kabupaten Lombok Utara - Bustanul Arifin; Adi Faizun; Sudariyah Sudariyah; Zubaedi Zubaedi; Masdani Masdani; Apriana Asdin; Suparlan Suparlan; Nining Pratiwi; Baiq Siti Hajar; Sadam Husen; Suhirman Jayadi (PT. ALHAFI BERKAH INDONESIA, 2023)
This service activity is intended to improve managerial abilities and services to the public as well as concern for the environment in the form of discussions with various elements packaged in the form of workshops followed by tree planting as a concrete step in caring for nature and the Islamic boarding school environment which in turn has an impact on air quality and coolness in the environment. Islamic boarding school environment. The method used was discussion and demonstration of tree planting in the Nurul Iman NW Bentek Islamic boarding school environment. This workshop contributed ideas regarding improving the management of Islamic boarding schools, planting trees on Islamic boarding school land according to the name of the planter. This service activity resulted in several conclusions: Pondok policy stakeholders continue to strive to increase their own potential to develop better Islamic boarding schools, Workshop activities increase knowledge for participants and students to continue to improve their knowledge and attitude of loving nature, and Planting productive trees is very effective in improving air quality. health, coolness, comfort and beauty in the Islamic boarding school environment.